Thermal effect investigation and passively Q-switched laser performance of composite Nd:YVO4 crystals. (May 2015) - Li, Shixia; Li, Yufei; Zhao, Shengzhi; Li, Guiqiu; Wang, Xiaomei; Yang, Kejian; Li, Dechun; Li, Tao
Abstract: Diode-pumped continuous-wave (CW) and passively Q-switched composite Nd:YVO4 lasers are presented by using Cr 4+ :YAG as saturable absorber. The temperature distributions and thermal focal lengths in three Nd:YVO4 crystals are numerically analyzed by a finite element method and the results show that diffusion-bonding composite crystals can effectively reduce the thermal lens effect. CW and passively Q-switched laser performances are experimentally investigated. The maximum CW output power of 3.35 W with an optical slope efficiency of 54.6% was obtained by Nd(0.1 at%):YVO4 /Nd(0.5 at%):YVO4 /Nd(1.0 at%):YVO4 composite crystal under an incident pump power of 6.52 W. The largest single pulse energy of 4.4 μJ with a pulse duration of 22 ns at a 166 kHz pulse repetition rate was also achieved. Highlights: The focal lengths of the composite and conventional Nd:YVO4 crystals have been studied. The composite crystal could effectively reduce the thermal lens effect. The laser performance of the composite crystal is superior to the single crystal. The combination of different composite crystals and output coupler can get the needed laser performance.